KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PROSES PEMBELAJARAN PAI DI SMP MUAMMADIYAH GORONTALO UTARA - Febrianto Hakeu; Ritmon Amalah; Cutri A. Tjalau; Ridwanto Djahuno (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study examines the leadership role of the principal in improving the quality of the PAI learning process at SMP Muammadiyah North Gorontalo. This study aims to find out about the functions and duties of school principals in improving the quality of the learning process of Islamic religious education at SMP Muhammadiyah North Gorontalo. The type of research used in this study is qualitative research, which is a type of research that provides a picture or phenomenon or symptom of a particular situation, both in the form of attitudes, conditions, ways that are being researched, so that the data obtained in the form of words and behaviors that are not expressed in the form of numbers and statistical numbers but remain in a qualitative state oriented to the leadership of the principal in improving the quality of the process PAI learning at SMP Muhammadiyah Kwandang North Gorontalo. The results of this study show that school principals play an essential role as educational leaders that influence the quality of PAI learning. The leadership strategies implemented include providing facilities and infrastructure, teacher training, and creating a conducive learning environment. Effective leadership of the headmaster was identified as a critical factor in improving the quality of Islamic religious education in the school. The implication of this research is the need for greater attention to the leadership development of school principals to support the improvement of the quality of the PAI learning process in Islamic educational institutions.